2013
DOI: 10.4149/bll_2013_040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iloprost on erythrocyte deformability in rat’s lower extremity undergoing an ischemia reperfusion injury

Abstract: Aim: Ischemia reperfusion injury (I/R) in lower extremity is a frequent and important clinical phenomenon. The protective effect of iloprost on local and distant organ injury due to I/R has been well documented but its effect on erythrocyte deformability needs further investigation. Our aim was to investigate the effect of iloprost on erythrocyte deformability in the infrarenal aorta of rats undergoing I/R. Materials and methods: Our study was conducted with 18 Wistar albino rats. Rats were divided into the 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The present study compared them and showed that PG analogs iloprost and alprostadil were almost equally effective in preventing I/R injury in skeletal muscle. Iloprost is a stable long-acting analog of PGI 2 and exerts cytoprotective effects mediated by several possible mechanisms, including vasodilation, membrane stabilization (7), reduced ROS production, antiplatelet activity (3,5), increased red cell deformability (20), and inhibition of leukocyte-endothelial adhesion (1,21). It also regulates microcirculation by decreasing the levels of proinflammatory cytokines (1).…”
Section: Discussionmentioning
confidence: 99%
“…The present study compared them and showed that PG analogs iloprost and alprostadil were almost equally effective in preventing I/R injury in skeletal muscle. Iloprost is a stable long-acting analog of PGI 2 and exerts cytoprotective effects mediated by several possible mechanisms, including vasodilation, membrane stabilization (7), reduced ROS production, antiplatelet activity (3,5), increased red cell deformability (20), and inhibition of leukocyte-endothelial adhesion (1,21). It also regulates microcirculation by decreasing the levels of proinflammatory cytokines (1).…”
Section: Discussionmentioning
confidence: 99%
“…Temporary abdominal aorta clamping and removal of the clamp to reperfuse the lower extremities for 120 min has been defined as the IR rat model (10,11).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…9 , 10 ILO exercises its vasodilatory effect by preventing platelet aggregation. 8 , 11 Another vasodilatory agent that acts via nitric oxide (NO) is sildenafil (SIL). 12 NO levels increase during ischaemia.13 During reperfusion, NO levels are elevated,13 caused by the vasodilator effect of SIL.…”
Section: Aimmentioning
confidence: 99%